(untitled) (Research, Society and Development, 2023)
The yellow passion fruit (Passiflora edulis f. flavicarpa) is a tropical fruit originating in Brazil, this country being the largest consumer and producer market, responsible for about 90% of world production. Despite the economic importance of this fruit, associated with the use of its pulp as a raw material for the food industry, about 65% of the total weight of the fruit is not used, with seeds and peels being discarded. The fixed oil extracted from the passion fruit seed is rich in minerals, tocopherols, carotenoids, polyphenols, tri-/di-/monoglycerides and essential fatty acids, outstanding characteristics for several industries. In this context, the present work had as objectives: to extract the oil from the passion fruit seed; to characterize its fatty components by Nuclear Magnetic Resonance and High-Performance Liquid Chromatography Tandem Mass Spectrometry; evaluate the antioxidant activity, acidity index, and acidity in oleic acid. The oil extracted in this work presented a chemical composition similar to that predicted in the literature for fatty acids: linoleic acid (43.6-49.15%), followed by oleic acid (13.8-16.12%), stearic acid (21. 76-26.5%), palmitic (11.28-13.8%), and linolenic (1.6-2.3%). In addition, it presented acidity (0.51 ± 0.04 - 1.73±0.02%) and acidity index (1.03±0.42 - 3.44±0.04 mg KOH/g) within the stipulated by Brazilian legislation for crude oils; regarding its antioxidant potential, the acetone extract (72.67±2.02%) showed greater activity when compared to the hexane extract (42.18±0.185%). The results suggest that passion fruit seed oil is a high-quality vegetable oil with possible applicability as a food additive or in cosmetic and pharmaceutical products.